(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Increased blood pressure (BP) is one of the most significant epidemiological, medical, social, and economic consequences of problems. The results of many studies indicate that in one-third of people in Ukraine, the level of BP exceeds 140/90 mm Hg, it is increased. There is a contradiction between the need to adhere to the current level of therapy, which involves the use of new, as a rule, expensive techniques and drugs, and the constant lack of funding for health care. Materials and Methods: Methods of statistical description, systematic, sociological, economic, and statistical analysis, including variational statistics, correspondence questionnaires, and expert assessments, were used in the research process. The study included 1568 patients diagnosed with hypertension. As a result of the pharmacoepidemiological analysis, it was shown that the most often antihypertensive monotherapy is performed for younger patients with initial lower BP values. Results: A more detailed analysis of the antihypertensive activity of drugs belonging to the main pharmacological groups was performed with arterial hypertension monotherapy. Therefore, it is important to analyze the therapeutic efficacy of antihypertensive drugs from different clinical and pharmacological groups, safety, and their impact on the wellbeing of patients. Discussion and Conclusion: Analysis of the structure of prescriptions revealed the dominant positions of Agriculture Commercialization Equity Fund drugs, and, above all, drugs enalapril, among patients with hypertension in all study groups, regardless of age and gender, as well as regimens of antihypertensive therapy. A retrospective study of the antihypertensive effect of drugs from different clinical and therapeutic groups revealed no significant differences, but significant differences were noted when comparing the original drugs with their reproduced analogs (generics)